2000
DOI: 10.3168/jds.s0022-0302(00)74875-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Cure after Therapy of Clinical Mastitis Caused by Staphylococcus aureus

Abstract: One hundred and fifty-nine cases of clinical Staphylococcus aureus mastitis were analyzed to detect factors associated with bacteriological cure after therapy. On 100 Dutch dairy farms, data were collected from four clinical trials with five intramammary treatment regimes designed to treat beta-lactamase-positive pathogens. Infected quarters were treated three times, with a 12-h interval between treatments. Treatment was extended for 2 d if results of the trial treatment were, according to the owner, not satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
4
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(191 citation statements)
references
References 17 publications
13
154
4
20
Order By: Relevance
“…Cure and re-infection during the dry period of CNS cases, however, could not be ruled out, as milk samples were only collected at drying off and after calving and not during the dry period. The cure rate during the dry period of non-agalactiae pathogenic streptococcal IMI was reported to be between 77 % and 90 % 14,53,59 , which correlates with the high cure rate found in this trial. However, the sample size was very small.…”
Section: Cure Ratesupporting
confidence: 76%
See 2 more Smart Citations
“…Cure and re-infection during the dry period of CNS cases, however, could not be ruled out, as milk samples were only collected at drying off and after calving and not during the dry period. The cure rate during the dry period of non-agalactiae pathogenic streptococcal IMI was reported to be between 77 % and 90 % 14,53,59 , which correlates with the high cure rate found in this trial. However, the sample size was very small.…”
Section: Cure Ratesupporting
confidence: 76%
“…Sandholm 46 reported that each month a STA infection persisted in the udder, the prognosis worsened by 20 % if the original cure was 100 %. The cure rate of STA decreases with the age of the cows (from 81 % for cows <48 months to 55 % for cows >96 months) and with the number of infected quarters (from 73 % for 1 infected quarter to 56 % for 4 infected quarters) 42,46,53 .…”
Section: Cure Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for bacteriological cure of Staphylococcus aureus infections following antibiotic treatment were reported previously. They included age, number of infected quarters, quarter location and stage of lactation and severity of the inflammation (Sol et al, 2000;Barkema et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The IRCM and BMSCC levels are not necessarily correlated (Barkema et al 1998a). Still, even when clinical cure after treatment is achieved, bacteriological cure is rarely better than 70% (Sol et al 2000;Pinz on-S anchez et al 2011). Indeed, CM cases might develop into subclinical mastitis characterized by an elevated SCC in the months thereafter and thus potentially increasing the BMSCC.…”
Section: Incidence Rate Of Clinical Mastitismentioning
confidence: 99%